Pemberdayaan Masyarakat Melalui Revitalisasi Nasi Berkat Berwadah Besek di Kampung Budaya Polowijen - Dian Candra Dewi; Gunarianto; Nasharudin Mas; Emilia Johansyah Budiarsono; Nadifa Fania Khuluqiya; Novalita Wahyu Rahmadani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
Polowijen Cultural Village is one of the thematic villages which is a tourist destination in Malang City. However, the renewal of local heritage in this village still does not have identification so there will be a rebranding of the Nasi Berkat renewal in the village. The aim of this update is to increase culinary appeal and preserve local heritage. Based on statistical data from the Malang City Culture and Tourism Office, the number of visitors to Polowijen Cultural Village shows a significant increasing trend. In 2015, the number of visitors only reached 1,500 people, but in 2022, there will be an increase of more than 1,566% to reach 25,000 people. This increase shows that efforts to develop this cultural village are starting to produce extraordinary results. This update involves various steps, from identifying local ingredients to promoting culinary destinations. This program is implemented through a rebranding method which includes: (1) Strengthening Identity and Quality, (2) promotion and marketing, (3) Monitoring and evaluation. This dedication notes the update method, results, and expected implications. This article provides a detailed look at successful update methods and hopes for the future. It can also be a source of inspiration for other communities looking to strengthen their local heritage through culinary innovation, while still upholding traditional values.